Pola Sebaran dan Kelimpahan Hiu Berjalan Halmahera (Hemiscyllium halmahera) di Teluk Weda Maluku Utara, Indonesia - Mu’min Mu’min; Nebuchadnezzar Akbar; Abdurrachman Baksir; Irmalita Tahir; Rommy M. Abdullah; Yunita Ramili; Firdaut Ismail; Rustam E Paembonan; Ikbal Marus; Eko S Wibowo; Hawis Madduppa; Beginer Subhan; Iswandi Wahab (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2021)
The Halmahera walking shark is a nocturnal species that lives at the bottom of waters and is a species endemic to North Maluku. Weda Bay is one of the largest bays on the island of Halmahera and contains marine resources and high diversity. The aims research was analyze the distribution pattern and abundance of Halmahera walking shark at that location. The research was conducted in September - November 2020. The sampling in Weda Bay, is carried out in two methods, (1) catch of nets with a mesh size of 2,5 cm stretched from the mangrove ecosystem, seagrass to coral reefs with a length of ± 50 meters and a height of 1,5 meters, (2) hand sampling equipment namely the sample catch it by hand with transect area (50x50m2) or 0,25 ha using basic diving equipment (snorkeling) to a depth of 3 meters at high tide in the night. Distribution pattern data analysis used Morisita Index and abundance analysis used reef fish abundance equation. Results the research found 28 individuals, namely 17 females and 11 males. There are 2 distribution patterns of the Halmahera epaullette shark, namely Grouping and Random. The clustered distribution pattern is found at stations 1, 2 and 4, while the random distribution pattern is found at station 3. Overall the distribution pattern of the Halmahera walking shark in Weda Bay is grouped. The highest abundance of Halmahera walkingshark was at station 1, namely 17,33 ind/ha and the lowest abundance at stations 3 and 4 was 5,33 ind/ha. The highest abundance is at station 1, this is because the habitat is still very good from the mangrove, seagrass and coral reef ecosystems to find food and the growth of the Halmahera walking shark.